Biomass-derived carbon nanostructures and their applications as electrocatalysts for hydrogen evolution and oxygen reduction/evolution - Maliutina, Kristina Mikhailovna; Omoriyekomwan, Joy Esohe; He, Chuanxin; Fan, Liangdong; Folli, Andrea (Frontiers in Environmental Engineering, 2023)
Biomass derived electrocatalysts with rationally designed activity, selectivity, and stability present a major sustainable approach for the electrochemical production of fuels and value-added chemicals. This review presents recent advances in the field of biomass-derived electrocatalytic nanostructures for the hydrogen evolution reaction (HER) and the oxygen reduction and evolution reactions (oxygen reduction reaction and oxygen evolution reaction), that are subject of major research efforts, as well as public and private investment, as they will play a crucial role in the energy transition and in achieving net zero carbon emissions. The review summarises experimental and theoretical investigations aiming at tuning electrocatalytic performances of sustainable C-based nanostructured materials, and present opportunities for future commercialization of innovative energy materials and applications. In reviewing relevant literature in the field, we focus on the correlation between electrocatalytic activity/selectivity and synthesis methods, composition, physical chemical characteristics, in the attempt to uncover a clear structure-activity relationship. Furthermore, this study provides a critical comparison of the different electrocatalysts in light of their catalytic mechanisms, limiting phenomena, and practical applications for sustainable future technologies.